The English Teacher’s Perspective and Challenge on Implementing Merdeka Curriculum - Indah Lestari (RETORIKA: Jurnal Ilmu Bahasa, 2023)
In navigating the complexities of implementing the Merdeka Curriculum, English teachers find themselves at the forefront of educational innovation. The English teacher’s role becomes pivotal in sculpting an effective learning experience within the framework of the Merdeka Curriculum. This study is aimed to investigate the English teachers’ perspective and challenge on implementing Merdeka Curriculum in English teaching and learning process. This study delves into the English teachers’ perspective and all their challenges when they implemented Merdeka Curriculum. Through qualitative descriptive, the study aims to shed light the various perspectives and challenges encountered by English teachers, providing valuable insights for curriculum improvement and professional development in language action. Interviewing three English teachers who teach at madrasah which becomes pilot project for implementing Merdeka Curriculum, subsequently, the data is obtained indicating that they hold the perspective that the implementation of the Merdeka Curriculum in English language learning has advantages in achieving material targets without rushing and in fostering student engagement, which is a requirement of the Merdeka Curriculum. According to them, these two aspects are positive outcomes of implementing the Merdeka Curriculum in English language learning. However, having positive aspects does not mean there are no challenges. The research subjects in this study stated that the biggest challenges in implementing the Merdeka curriculum in English language learning are understanding and accommodating the diversity of students’ character and learning styles, which will impact the determination of an effective model for English language instruction.